Factors affecting learning the Russian language - Komilova Muyassar Mavjudovna (Zien Journals, 2022)
The article discusses the factors, problems and difficulties affecting the study of Russian in Uzbek groups, and comments on the existing textbooks. Suggestions were made for the development of students' Russian language skills in military academies.
Keywords: Military education system; problems; Russian as a foreign language; influencing